A new name for Euphorbia linguiformis Hett., Haev. & Spannring (Euphorbiaceae) - Haevermans, Thomas; Hetterscheid, Wilbert L.a. (Phytotaxa, 2021)
The species Euphorbia linguiformis Hetterscheid, Haevermans & Spannring (2021: 16) has been named erroneously in a recent publication (Haevermans & Hetterscheid 2021) on Euphorbia Linnaeus (1753: 450), not realising that this epithet was already in use for another taxon, Euphorbia linguiformis McVaugh (1961: 184), making our new species an illegitimate later homonym (ICN Art. 53.1, Turland et al. 2018). We therefore propose a new name for our taxon here